Persistence of Cerebral Palsy Diagnosis: Assessment of a Low-Birth-Weight Cohort at Ages 2, 6, and 9 Years. (March 2016) - Korzeniewski, Steven J.; Feldman, Judith F.; Lorenz, John M.; Pinto-Martin, Jennifer A.; Whitaker, Agnes H.; Paneth, Nigel
We examined the stability of nondisabling and disabling cerebral palsy at age 2 in a longitudinally followed tri-county low-birth-weight (<2000 g) birth cohort. A total of 1105 newborns were enrolled, 901 (81.5%) survived to age 2, and 86% (n = 777) were followed up. Of the 113 cerebral palsy diagnoses at age 2, 61 (9% of the cohort, n = 61/777) had disabling cerebral palsy and 52 (7%, n = 52/777) had nondisabling cerebral palsy. Of 48 followed children diagnosed with disabling cerebral palsy at age 2, 98% were again classified as having cerebral palsy at school age, and 1 had an uncertain cerebral palsy status. By contrast, 41% (n = 17) of the 43 children diagnosed with nondisabling cerebral palsy at age 2 were classified as not having cerebral palsy. Of the 517 followed children who were not diagnosed with cerebral palsy at age 2, 7% (n = 35) were classified as having late emerging nondisabling cerebral palsy at school age.